CFD simulation of biodiesel production using mixed flow impeller in baffled and unbaffled stirred vessel - Adeyemi, Nabeel A.; Mohiuddin, A. K. M.; A. Aziz, A. Rashid; Anbese, Yohannes Tamirat; F., Firmansyah; Husaini, Muhamad (2012)
In this paper, the numerical modeling of alkali-catalyzed waste cooking oil (WCO) transesterification in a 2-L stirred tank reactor (STR) is discussed. Based on the Navier-Stokes equation, the liquid flow in the STR was resolved using unstructured, non-uniform mesh with the sst- κ-ω, κ-ε and RSM turbulent models. The PIV velocity data was used to verify the appropriate turbulent model for a computational fluid dynamics (CFD) simulation. The numerical results were in agreement with experimental PIV. CFD simulation executed for the transesterification of WCO, indicate the reaction efficiency in biodiesel yield with a mixed flow impeller. The reactive species were modeled as diffusive scalar and set in a eulerian-eulerian framework and the numerical results have also been verified for the reaction condition for 1 and 2-L STR. The effects of hydrodynamic were verified which indicate that mixed flow impeller and fluid velocity have more significant impacts on yield. Yield from the numerical model varied by about 13 and 27% with the RSM model.